Polimorfismo da Clorpropamida investigado através de Espectroscopia Vibracional - Caetano, Márcia de Windson Costa (2006)
Chlorpropamide (C10H13ClN2O3S, (1-[4-chlorobenzenesulphonyl]-3-propyl urea)) is a drug used to treat type II diabetes (non-dependent of insulin), especially when the diabetes can not be controlled by alimentary regimes. The polymorphism of this drug is widely documented exhibiting at least five crystalline forms. In this work, we present a vibrational study of four of these polymorphs by using Raman, infrared and near-infrared spectroscopies. The objective of this vibrational investigation is to correlate the vibrational modes with the possible crystalline structures, as well as, to evaluate these methods as a tool for identification and quality control of raw materials and formulated products. In order to provide a detailed characterization we also applied thermal analyses and x-ray powder diffraction techniques to identify the crystalline forms. Finally, the assignment of the bands observed in the vibrational spectra in terms of the normal vibrational modes was performed with the help the quantum mechanical calculations based on the density functional theory. These results allow us to investigate the conformational stability of chlorpropamide establishing correlations with the polymorphism of this drug.